Evaluación de las prescripciones de medicamentos de control especial en la unidad de cuidados intensivos de un hospital de referencia en Bogotá. - Flórez Buitrago, Astrid Catalina
Objective Controlled medication is regulated by Fondo Nacional de Estupefacientes of the Colombian government. This means that the correct way to fill medical prescriptions in is a matter of regulation. The goal of the present study is to evaluate the prescriptions of controlled medication in the ICU (intensive care unit as it is in Spanish in the original) of a reference hospital in Bogotá. Method: Descriptive retrospective transversal study developed during three months, from april to june, 2016. 1483 controlled medication prescriptions were analyzed and tested in such ICU. Prescriptions were assessed in terms of integrity, legibility, alteration and abbreviation use following variables that constitute the prescription itself. Results: Integrity in 14,76 % (n=219) prescriptions showed a higher percentage of information omission; for variables such as “treatment time” 34,86 % (n=517) and “route of administration” 23,74% (n=352); variables such as “patient ID” and “prescriber ID” allowed us to identify a wide data prescription-fill-in percentage, 55,7 % and 41,4 % respectively. From 84,7 % of the calculated mean for integrality, which includes the addition of full and partial fill-in-prescription variables, thus, prescription legibility was stablished in a 99,27 %, which, in general, indicates a good readability in the registered variables. This analysis allowed us to identify abbreviation use in a 99,06 % (n=1469) of controlled medication prescription assessed. Conclusions:We recommend to standardize and socialize the fill-in criteria of controlled medication prescriptions processed in the ICU, which should follow clear and efficient fill-in protocols.